Assessment of nutritional status and other associated factors of lactating mother at Gangni Pauroshava in Meherpur district, Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2017)
The present study was to provide information about the nutritional status of lactating women as well as proffer solutions that are aimed at improving maternal nutrition in the study area. The study area was Gangni union of Meherpur district. 105 exclusively breastfeeding women aged 16-35 years old were initially enrolled in the study. Of these study lactating women completed 24h dietary recall food intake. The findings was about 16.2% lactating mothers were under 19 years, 53.3% respondents were between the ages of 20-25 years, 23.8% respondents were between the ages of 26-30 years and 37.1% lactating mothers had completed primary education. About 95.2% respondents were housewife and 4.8% respondents were service holders. The finding was 56.2% respondents have one child and 38.1% respondents have 3 family members, 43.8% respondent has 4 family members. About 7.6% respondents are underweight, 55.2% respondents are normal, 33.3% respondents are overweight and 3.8% respondents are obese. Total 7.6% respondents are underweight, 55.2% respondents are normal, 33.3% respondents are overweight and 3.8% respondents are obese where 5.7% respondents under 19 year aged and 1.9% respondents over 30 year aged are underweight. About 40% respondents got surgerian delivery where 60% respondents got normal delivery. It was found that 100% respondents maintain hygiene such as washing hands before eating foods, washing hands after using bathroom, brushing teeth regularly, avoiding nasty foods etc.Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 35-44